De l’acceptabilité sociale au développement local résilient - Emmanuel Raufflet (VertigO, 2014)
In recent years, questions related to the social license to operate, particularly in the extractive sector, have become important issues for businesses, as projects direct investors and operators, as well as for governments, as promoters of local and regional economic developement projects. Our key argument is that resilient local development thinking should replace the sole goal of attaining a social license to operate. We contend that the mere focus on the social license to operate—as an approach based on preventing and solving conflicts, most often in the short term – is too limited. Therefore, this should be replaced by a wider vision towards the resilient local development based on three pillars: economic diversification, local social cohesion, and environmental sustainability. This contributions of this paper contribution are tow, namely to critically assess the notion of project social acceptance based on the literature from the natural resources sector, and to identify a new focus on resilience local development beyond the sole focus on social license to operate.